2011
DOI: 10.1177/0273475311410846
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Impact of Online Resource Materials on Student Self-Learning Strategies?

Abstract: The purpose of this article is to examine how students are incorporating online resources into their self-regulated learning strategies. The process of developing these learning strategies and the importance of these strategies has been widely researched, but there has been little empirical research into how the students are affected by online environments. This preliminary study focused on the relationship between the use of online resources and the students’ overall outcome in the subject. The data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
1
11
1
Order By: Relevance
“…Moreover, students perceive well-crafted online videos, exciting in-class activities, flexibility, convenience, and availability of teacher for questioning as effective reverse teaching. These benefits are consistent with studies, emphasizing the use of online materials (Dowell and Small, 2011), thus forming an important part of the blended learning experience (Friesen, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, students perceive well-crafted online videos, exciting in-class activities, flexibility, convenience, and availability of teacher for questioning as effective reverse teaching. These benefits are consistent with studies, emphasizing the use of online materials (Dowell and Small, 2011), thus forming an important part of the blended learning experience (Friesen, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…While student grades remained unchanged, their enjoyment and willingness to study may have improved, as suggested by the positive feedback obtained. Furthermore, Dowell and Small [3] found that increased learning strategies improved grades, contradicting this study's findings. Perhaps this difference is due to iBooks only being made for the Cardiology-Pulmonary-Renal block, as opposed to covering the entire curriculum.…”
Section: Dear Editorcontrasting
confidence: 99%
“…In the present case, the students were engaged in the use of technology, a customer journey mapping tool. The strategic use of technology to solve a problem had a positive impact on the teacher's and students' experience (Bitner, Ostrom, & Burkhard, 2012;Dowell & Small, 2011) and helped foster deeper learning (Canhoto & Murphy, 2016). As called for by these last authors, the class includes feedback mechanisms for students, invites them to discuss their decisions and reflects on the meaning of the data results.…”
Section: Resultsmentioning
confidence: 99%